SP7.1 Virtual classroom proficiency-based progression for robotic surgery training (VROBOT): a prospective, cross-over, effectiveness study. (9th August 2022) - Patel, Sonam; Nathan, Arjun; Georgi, Maria; Hang, Man Kien; Fricker, Monty; Sridhar, Ashwin
Abstract: Aims: Robotic surgery is an evolving surgical technique, requiring specialist training. The standardised Fundamentals of Robotic Surgery (FRS) curriculum incorporates proficiency-based modules to certify the skills of novice trainees. However, the curriculum is self-directed and non-interactive. We aim to determine the effectiveness of interactive virtual classroom training (VCT) in concordance with the FRS for robotic skills training. Methods: 11 novice surgical trainees were randomly allocated to two training groups. Both groups completed a one-week robotic skills induction. In week two, Group A received training with the FRS curriculum and adjunctive VCT; Group B only received access to the FRS curriculum. In week three, the groups received the alternate intervention. The primary outcome was measured using the validated R-OSAT score. This was collected post-intervention at time point 1(end of week two) and time point 2(end of week three). Results: Participants attained higher mean proficiency scores with both the FRS curriculum and VCT, compared to the FRS curriculum alone. At timepoint 1, Group A achieved a greater mean proficiency score compared to Group B (44.80 vs 35.33, p=0.006). At timepoint 2, there was no significant difference in mean proficiency score in Group A from timepoint 1. In contrast, Group B, who received adjunctive VCT showed significant improvement in mean proficiency by 9.67points from timepoint 1 (95% CI 5.18–14.15, p=0.003). Conclusion: VCT is an effective training adjunct to the FRS curriculum for learning basic robotic skills. With the steep learning curve in robotic surgery training, VCT offers interactive learning and can increase training effectiveness and accessibility.